REKRUTMEN SUMBER DAYA MANUSIA MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI DI LINGKUNGAN CABANG PERUM BULOG PALEMBANG: REKRUTMEN SUMBER DAYA MANUSIA MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI DI LINGKUNGAN CABANG PERUM BULOG PALEMBANG - Liana, Wendy; Indriani (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
Human resources are the abilities possessed by every human being. Human resources consist of the intellectual and physical powers of every human being, which means that the abilities of every human being are determined by their intellectual and physical powers. Human resources are the first and foremost element in every activity carried out. However, an organization with a perfect work plan and sufficient costs and sophisticated equipment, if run by people with low abilities and inappropriate placement, will be difficult to achieve the desired goals. Human resource development is a long-term investment that is more oriented towards increasing employee work productivity in the future. Because it concerns the future, management must prepare a plan that is as precise as possible in order to achieve the target. Human Resource Planning is a decision-making step for the future taken by management to further ensure that the organization has the right workforce to occupy various positions, positions and the right jobs, at the right time in order to achieve the goals and various targets that have been and will be set.